Exploring the Effects of a Neck Strengthening Program on Purposeful Soccer Heading Biomechanics and Neurocognition - Katelyn M. Waring; Edward R Smith; Gary P Austin; Thomas G Bowman (North American Sports Medicine Institute, 2022)
# Background Cervical (neck) strengthening has been proposed as an important factor in concussion prevention. The purpose of the study was to determine if a six-week cervical strengthening program affected neurocognition and purposeful soccer heading biomechanics. The hypothesis was that the neck strengthening program would improve strength, maintain neurocognition, and alter purposeful soccer heading biomechanics. # Study Design Randomized controlled trial. # Methods Twenty collegiate soccer athletes (8 males, 12 females, age=20.15±1.35 years, height=171.67±9.01 cm, mass=70.56±11.03 kg) volunteered to participate. Time (pre, post) and group (experimental, control) served as the independent variables. Four composite scores from the CNS Vital Signs computer based neurocognitive test (CNSVS; verbal memory, visual memory, executive function, reaction time) and aspects of heading biomechanics from inertial measurement units (xPatch; peak linear acceleration, peak rotational acceleration, duration, Gadd Severity Index \[GSI\]) served as the dependent variables. Each athlete completed a baseline measure of neck strength (anterior neck flexors, bilateral anterolateral neck flexors, bilateral cervical rotators) and CNSVS after heading 10 soccer balls at two speeds (11.18 and 17.88 m/s) while wearing the xPatch. The experimental group completed specific cervical neck strengthening exercises twice a week for six weeks using a Shingo Imara™ cervical neck resistance apparatus while the control group did not. After six weeks, the participants completed the same heading protocol followed by measurement of the same outcome variables. The alpha value was set to p\<0.05 *a priori*. # Results The interaction between time and group was significant for visual memory (F~1,17~=5.16, p=0.04, η^2^=0.23). Interestingly, post hoc results revealed visual memory decreased for the control group from pretest (46.90±4.46) compared to posttest (43.00±4.03; mean difference=3.90, 95% CI=0.77-7.03, p=0.02). Interactions for all other dependent variables were not statistically significant (p\>0.05). # Conclusions The cervical neck strengthening protocol allowed maintenance of visual memory scores but did not alter other neurocognitive measures or heading biomechanics. The link between cervical neck strengthening and concussion predisposition should continue to be explored. # Level of Evidence Level 1b